Parcours Problema Littérature : un dispositif didactique centré sur la théorie du questionnement - François Simon; Annette Schmehl-Postaï; Catherine Huchet (Nantes Université, 2015)
This article investigates the teaching-learning processes of analysizing and understanding literary texts in upper elementary courses. Within the theoretical framework of problem-oriented learning, which is closely linked to the theory of questioning and problematology, we develop a reflection on this specific didactic approach called "Parcours Probléma Littérature". This approach is tested by several teachers. Our approach is defined as a model of possibilities for the teaching-learning process considering analysis and comprehension and favours three major axes: an introduction into the literary work as a key-moment, chosen reading-modes and the cognitive regulation mediated by the teacher. In the article, we analyze two typical and recurrent situations of the regulative breaks: rephrasing and anticipating. The exposed didactic model puts the focus on the reader as individual. It is precisely the mediation between the reader's world and the world of the text which is at the core of the model. The "Parcours Problema Littérature" incites the teacher to ponder over his evaluation-attitude in order to facilitate the pupils' confrontation with new axiological, epistemic and rhetorical knowledge